The impact of vitamin D deficiency on some biochemical parameters and clinical outcome in Palestinian pregnant women during the first trimester - Saleh Nazmy Mwafy; Safaa Ramadan Abed El- Nabi; Mohammed Marwan Laqqan; Maged Mohamed Yassin (PLoS ONE, 2023)
Background and aim Vitamin D deficiency is widespread worldwide and associated with negative effects on maternal and neonatal health. This study aimed to evaluate the relationship between vitamin D and thyroid and parathyroid hormone levels in the first trimester of pregnancy. Material and methods This case control study included 200 participants aged (18–40) years divided into two groups; 100 pregnant females at the first trimester as case group, attending the main general clinical centers in Gaza strip, Palestine and 100 apparently healthy non-pregnant females as control group. Vitamin D, free thyroxine, free triiodothyronine, thyroid stimulating hormone, parathyroid, and the autoantibodies specific for thyroglobulin and thyroid peroxidase in serum were measured in all mothers and statistically analyzed using SPSS version 21 software. Results Serum vitamin D, TSH, anti-TPO, and anti-TG levels were significantly decrease while, parathyroid levels were non-significantly decreased in the first trimester of pregnancy compered to control group. The levels of fT4 were significantly increased and level of fT3 were non significantly increased among pregnant mothers compered to control group. Analyses using Pearson correlation coefficients showed positive correlations between vitamin D with fT4, fT3, Anti-TPO with P -value < 0.05 and negative correlations with mother age, TSH, PTH with P-value < 0.05 in early pregnancy. Conclusions Vitamin D deficiency among pregnant women in the first-trimester can be associated with thyroid, parathyroid parameters and thyroid autoantibodies with potential adverse consequences for overall health, emphasizing a routine monitoring and vitamin D supplementation prevention strategies to optimize maternal and fetal outcomes.